The activation of Chlamydomonas reinhardtii alpha amylase 2 by glutamine requires its N‐terminal aspartate kinase–chorismate mutase–tyrA (ACT) domain - Lisa Scholtysek; Ansgar Poetsch; Eckhard Hofmann; Anja Hemschemeier (Plant Direct)
Abstract The coordination of assimilation pathways for all the elements that make up cellular components is a vital task for every organism. Integrating the assimilation and use of carbon (C) and nitrogen (N) is of particular importance because of the high cellular abundance of these elements. Starch is one of the most important storage polymers of photosynthetic organisms, and a complex regulatory network ensures that biosynthesis and degradation of starch are coordinated with photosynthetic activity and growth. Here, we analyzed three starch metabolism enzymes of Chlamydomonas reinhardtii that we captured by a cyclic guanosine monophosphate (cGMP) affinity chromatography approach, namely, soluble starch synthase STA3, starch‐branching enzyme SBE1, and α‐amylase AMA2. While none of the recombinant enzymes was directly affected by the presence of cGMP or other nucleotides, suggesting an indirect binding to cGMP, AMA2 activity was stimulated in the presence of L‐glutamine (Gln). This activating effect required the enzyme's N‐terminal aspartate kinase–chorismate mutase–tyrA domain. Gln is the first N assimilation product and not only a central compound for the biosynthesis of N‐containing molecules but also a recognized signaling molecule for the N status. Our observation suggests that AMA2 might be a means to coordinate N and C metabolism at the enzymatic level, increasing the liberation of C skeletons from starch when high Gln levels signal an abundance of assimilated N.